2006
DOI: 10.1103/physrevlett.97.138102
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Self-Affinity and Polarized Light Scattering in the Born Approximation: A New Model for Precancer Detection

Abstract: Light scattered from biological tissues can exhibit an inverse power law spectral component. We develop a model based on the Born approximation and von Karman (self-affine) spatial correlation of submicron tissue refractive index to account for this. The model is applied to light scattering spectra obtained from excised esophagi of normal and carcinogen-treated rats. Power law exponents used to fit dysplastic tissue site spectra are significantly smaller than those from normal sites, indicating that changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
143
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 14 publications
1
143
0
Order By: Relevance
“…The spectral changes induced by the refractive index spatial correlation in tissue have also been theoretically analysed [9] and experimentally measured [29]. It was also found that modelling tissue structure in terms of refractive correlation function may provide new methods of diagnosing cancers [26]. And the power-law exponent of the backscattering spectrum is sensitive to the length scale at approximately 30-450 nm [36].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The spectral changes induced by the refractive index spatial correlation in tissue have also been theoretically analysed [9] and experimentally measured [29]. It was also found that modelling tissue structure in terms of refractive correlation function may provide new methods of diagnosing cancers [26]. And the power-law exponent of the backscattering spectrum is sensitive to the length scale at approximately 30-450 nm [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the existence of the spatial correlation of the refractive index of the medium, the spectrum of the scattered light in the far zone will be modified by a multiplicative factor that is proportional to the three-dimensional Fourier transform of the spatial correlation function of the random medium [29]. For tissue scattering, experimental data reveal that at the micrometre level [24] and submicrometre level [26,37,38], the spectrum of the scattered light is dominated by the fractal behaviour of tissue. Sheppard [23] also pointed out that the fractal tissue model may work best when one is concerned with details smaller than the typical size of organelles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations